348 PROGNOSTIC EVALUATION OF HEART FAILURE IN WOMEN: INSIGHT FROM THE MECKI SCORE DATABASE. (15th December 2022) - Salvioni, Elisabetta; Moscucci, Federica; Bonomi, Alice; Mapelli, Massimo; Paolillo, Stefania; Corrà, Ugo; Vignati, Carlo; Magrì, Damiano; Sciomer, Susanna; Agostoni, Piergiuseppe
Abstract: Background: Heart failure (HF) in women often assumes extremely peculiar characteristics. The risk stratification and prognostic evaluation of HF in women is a challenge for clinicians. The actual prognostic scores are, in fact, lacking a specific sex-oriented assessment. In HF women show better survival despite a comparatively low peak oxygen consumption (VO2 ) at cardiopulmonary exercise testing: this raises doubt about the accuracy of risk assessment in women. Previous studies on MECKI score database have demonstrated that female prognostic advantage is lost when sex-specific differences are correctly considered. The present analysis has the aim to identify parameters which could be differently associated to prognosis in men and women and to re-calibrate the MECKI score according to these differences. Methods: The new weights of the MECKI score variables according to gender, were calculated using the means of the 200 repetitions obtained to cross-validation procedure. The primary outcome of the study was the composite of all-cause mortality, urgent heart transplant and LVAD implant. The difference in predictive ability between the native and gender re-calibrated MECKI was calculated with the ROC curve at 2 years follow-up and calibration plot. Results: We retrospectively analyzed 7900 HF patients with reduced ejection fraction included in the MECKI score registry (61±13 years, 6456 M/ 1444 F, LVEF 33±10%, VO2 /kg 14.9±4.9 mL/min Kg). Patients follow up was: 4.05 years [1.72-7.47]. Table 1 presents the weights of the individual MECKI variables for males and females. The main differences have been detected for the intercept value, hemoglobin and Na + . We used these variables to recalibrate the algorithm of MECKI score. We obtained higher AUC for MECKI re-calibrated by gender than for Native MECKI (0.7893 vs. 0.7799, p=0.0194, Fig. 1 left panel). Moreover, the gender MECKI was better calibrated (Fig. 1, right panels). Conclusions: The calibration of MECKI Score according to gender specific differences improves the prognostic power and accuracy of mortality prediction at two years follow up.